Penerapan Tqm Dalam Peningkatan Kuaitas Pelayanan Prima di Kantor Desa Pulau Rantau Kecamatan Tanah Grogot Kabupaten Paser - Nuriyah Nuriyah; Muhammad Akbar; Karlina Karlina; Achmad Syahruddin; Rusmiati Rusmiati; Erni Susanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Pulau Rantau Village is one of the villages under the working area of ​​Tanah Grogot District. Community Service by providing material related to TQM so that village employees are able to carry out their duties and responsibilities well, namely by providing maximum service to every community who needs services at the village office. The target of implementing this activity is all employees at the Pulau Rantau Village Office, Tanah Grogot District, with the material of Implementing TQM in Improving the Quality of Excellent Service carried out through lecture and question and answer discussion methods. In this activity, the importance of cooperation between all village officials in providing services to the community is also conveyed, so that excellent quality service and satisfaction is felt by every community member who receives services at the village office.